Dollarization in Transition Economies : Evidence and Policy Implications - Vegh Gramont, Carlos; Sahay, Ratna (Washington, D.C. : International Monetary Fund, 1995)
After most restrictions on foreign currency holdings were relaxed in the early 1990s, foreign currency deposits in transition economies have been increasing rapidly. This paper takes a first look at the evidence on dollarization for 15 transition economies, and then discusses some key conceptual and policy implications. Depending on the institutional constraints, foreign currency deposits as a proportion of broad money reached a peak of between 30 and 60 percent in 1992-93. Unlike what has been observed in Latin America, however, dollarization has fallen substantially in the aftermath of successful stabilization plans in Estonia, Lithuania, Mongolia, and Poland. Since foreign currency deposits reflect mainly a portfolio choice, the fall in dollarization can be primarily attributed to higher real returns on domestic-currency assets, as a result of lower inflation and more market-determined interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet